2012
DOI: 10.1016/j.amepre.2012.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Weight Gain Following a Worksite Nutrition and Exercise Program

Abstract: Background Many employers are now providing wellness programs to help employees make changes in diet and exercise behaviors. Improving health outcomes and reducing costs will depend on whether employees sustain lifestyle changes and maintain a healthy weight over time. Purpose To determine if a 9-month maintenance intervention immediately following a 10-week worksite exercise and nutrition program would prevent regain of the weight lost during the program. Design RCT. Setting/participants In 2008, a tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(82 citation statements)
references
References 27 publications
2
79
1
Order By: Relevance
“…This is similar to other studies (17)(18)(19)(20)(21). The drop down menu is a limitation in this study because the goal options for physical activity far exceeded the recommendations whereas goal options for fruit and vegetable intake provided a maximum that was equal to recommendations.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…This is similar to other studies (17)(18)(19)(20)(21). The drop down menu is a limitation in this study because the goal options for physical activity far exceeded the recommendations whereas goal options for fruit and vegetable intake provided a maximum that was equal to recommendations.…”
Section: Discussionsupporting
confidence: 85%
“…While the analysis of the data for this study took place at the University of Rhode Island, the data was collected from eight participating institutions around the country. 20,30,45,60,75,90,105,120,135,150,165, or 180+ minutes (on average) per day. In addition there was an option for don't know/not sure minutes of exercise (subjects choosing this option were excluded from exercise analyses).…”
Section: Design and Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the high quality studies, less than half (7) reported significant improvement in any weight related outcome[12], [14], [16], [22], [23], [26], [29]. The same number of high quality studies reported no significant change in the outcomes[15], [17], [20], [21], [24], [25], [27] while the last high quality study reported worsening of the outcome, in this case an increase in body fat[28]. One of the trials [15] with no significant intervention effect was a 2 year follow-up on a study [26] that showed a significant reduction in weight-related outcomes at 6 months.…”
Section: Resultsmentioning
confidence: 99%